2022
DOI: 10.35882/jeeemi.v4i3.225
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study for Time-to-Event Analysis and Survival Prediction for Heart Failure Condition using Machine Learning Techniques

Abstract: Heart Failure, an ailment in which the heart isn’t functioning as effectively as it should, causing in an insufficient cardiac output. The effectual functioning of the human body is dependent on how well the heart is able to pump oxygenated, and nutrient rich blood to the tissues and cells. Heart failure falls into the category of cardiovascular diseases - the disorders of the heart and blood vessels. One of the leading causes of global deaths resulting in an estimated 17.9 million deaths globally every year. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A decision tree has been built to detect driver fatigue based on EEG data [23]. Mishra has conducted a study to compare the performance of decision tree to other machine learning techniques on survival prediction for heart failure conditions [24]. The decision tree method has been utilized in the medical industry to diagnose disorders such as stroke, merkel cell carcinoma, and diabetic patients [25]- [27].…”
Section: Figure 2 An Illustration Of Circumductionmentioning
confidence: 99%
“…A decision tree has been built to detect driver fatigue based on EEG data [23]. Mishra has conducted a study to compare the performance of decision tree to other machine learning techniques on survival prediction for heart failure conditions [24]. The decision tree method has been utilized in the medical industry to diagnose disorders such as stroke, merkel cell carcinoma, and diabetic patients [25]- [27].…”
Section: Figure 2 An Illustration Of Circumductionmentioning
confidence: 99%
“…Epidemiological analysis showed that diabetes is an independent risk factor for the development of heart failure in both men and women 3 . Indeed, the prevalence of heart failure is fourfold higher in the diabetic population than in the general population 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Using one or two feature selection techniques can able to rectify the most relevant features for identifying the death cases. Then, the authors [8]- [10] utilized a famous data balancing technique named synthetic minority oversampling technique (SMOTE) to overcome data imbalance techniques and obtained prediction accuracy of 92.6%, 91.23%, and 83.33%, respectively. But SMOTE potential to generate noisy and uninformative samples [11].…”
Section: Introductionmentioning
confidence: 99%